2010
DOI: 10.1038/onc.2010.516
|View full text |Cite
|
Sign up to set email alerts
|

The actin-associating protein Tm5NM1 blocks mesenchymal motility without transition to amoeboid motility

Abstract: Cell migration is an integral component of metastatic disease. The ability of cells to transit between mesenchymal and amoeboid modes of migration has complicated the development of successful therapies designed to target cell migration as a means of inhibiting metastasis. Therefore, investigations of the mechanisms that regulate cell migration and render cells stationary are necessary. Tropomyosins are actin-associating proteins that regulate the activity of several effectors of actin filament dynamics. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 37 publications
4
31
0
Order By: Relevance
“…In agreement with previous studies demonstrating that tropomyosin overexpression reduces cellular motility (38)(39)(40), we observed that human Tpm1 expression significantly diminished the speed of HeLa cell migration (Fig. S4 C and D).…”
Section: Tpm1 Overexpression Partially Restores Actin Cytoskeletonsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies demonstrating that tropomyosin overexpression reduces cellular motility (38)(39)(40), we observed that human Tpm1 expression significantly diminished the speed of HeLa cell migration (Fig. S4 C and D).…”
Section: Tpm1 Overexpression Partially Restores Actin Cytoskeletonsupporting
confidence: 93%
“…Tropomyosin expression increased or decreased focal adhesion area (38)(39)(40), consistent with the idea that maximal migration rates require the specific organization of the focal adhesions and actin filaments. Similarly, our findings provide evidence indicating that the tight regulation of tropomyosin and the amount of acetylated Tpm1 is necessary for maximal cellular motility (Fig.…”
Section: Tpm1 Overexpression Partially Restores Actin Cytoskeletonsupporting
confidence: 80%
“…Cell lines were maintained in Dulbecco's modified eagle's medium (DMEM) supplemented with 10% FBS. Growth of cells in 3D collagen gels, media for live imaging, and invasion assays through 3D collagen gels was based on protocols previously reported to identify invasion plasticity (21) and as we have previously used (22). The following antibodies were used: anti-NEDD9 (ImmuQuest; clone 2G9 and Cell Signaling Technology, clone 29G), antipan-Rac (#610650 BD Bioscience), anti-HSP70 and anti-a-tubulin (Sigma-Aldrich), and horseradish peroxidase-conjugated anti-mouse and anti-rabbit (Amersham and Biorad) and anti-rat Alexa-Fluor 647 conjugate (Molecular Probes; Invitrogen).…”
Section: Cell Culture and Antibodiesmentioning
confidence: 99%
“…Thus, cells with altered tropomyosin expression profiles display differential actin filament stability (2,4,13). Moreover, tropomyosin isoform expression is correlated with different focal-adhesion morphology (4,14) and isoform-specific effects on cell migration (2,4,(14)(15)(16). The tropomyosin isoform Tm5NM1 is ubiquitously expressed (17), and elevated expression inhibits both 2-dimensional (2D) (2,4) and 3D (16) cell migration.…”
mentioning
confidence: 99%
“…Tm5NM1-mediated actin filament stabilization is accompanied by reduced activation of the nonreceptor kinase Src (16). Src is a major regulator of focal-adhesion disassembly (18,19), and depletion of Src family kinase activity reduces cell motility (20) and causes enlarged and stabilized focal adhesions (18,21).…”
mentioning
confidence: 99%